If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -9) + 4(x + 3) = 0 Reorder the terms: 3(-9 + x) + 4(x + 3) = 0 (-9 * 3 + x * 3) + 4(x + 3) = 0 (-27 + 3x) + 4(x + 3) = 0 Reorder the terms: -27 + 3x + 4(3 + x) = 0 -27 + 3x + (3 * 4 + x * 4) = 0 -27 + 3x + (12 + 4x) = 0 Reorder the terms: -27 + 12 + 3x + 4x = 0 Combine like terms: -27 + 12 = -15 -15 + 3x + 4x = 0 Combine like terms: 3x + 4x = 7x -15 + 7x = 0 Solving -15 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 7x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 7x = 0 + 15 7x = 0 + 15 Combine like terms: 0 + 15 = 15 7x = 15 Divide each side by '7'. x = 2.142857143 Simplifying x = 2.142857143
| 0.29(x+50)-6=0.4(3x+20) | | (x+3)+(y+6)=46 | | 4.2d=-10.5 | | 7k+5=5(1-7k) | | 3(x-4)+4(x+3)= | | 48-2x=x | | .25x-0.75=-0.25x+3.25 | | x-16+2x-85+.5x+8=180 | | 7-14x=15x-16 | | 3x+y=78 | | -27t=-21.6 | | 14x^2+7x-21=0 | | -5y=8.5 | | 5t^2+15t+10=0 | | 3k-k+3=k-7 | | -4.72x=65 | | -4x^2+4x-7=0 | | 12+5z=13+5z | | 14-4t=2(17-t) | | 2(48)=x | | (x-1)(x+5)=x+4x-2 | | 2(x)=48 | | 0.089x-0.32+0.001(5-x)=0.231 | | -37=8y | | 2(h-5)h=h-10 | | 8-3x=-4x-12 | | 2(x)-8=40 | | 28-5t=2t | | 4-2=y+10 | | 3x+2=2x-11 | | 2y^2-3y-20=0 | | 5x-2=6x+3 |